Hot and Cold: Coexistent Graves’ and Hashimoto’s Thyroiditis: A Case Series - Luthfiyya Syafiqa Tahany; I Made Wisnu Wardhana; Darma Irawan (International Medical Journal Corp. Ltd, 2024)
Introduction: Autoimmune Thyroid Disease (AITD) is a common endocrine disorder, with Graves’ Disease (GD) and Hashimoto’s Thyroiditis (HT) as its primary manifestations. Both conditions share overlapping pathophysiological mechanisms, often leading to diagnostic challenges. This case series aims to describe and analyze cases of hyperthyroidism with complex clinical and laboratory features, suggesting GD, HT, or both. Case Reports: Three patients (Mr. D, 42 years old; Mr. RKA, 47 years old; Ms. MMR, 26 years old) presented with clinical manifestations of hyperthyroidism. Laboratory examinations consistently showed low or very low TSH levels, along with increased Free T3 (FT3) and Free T4 (FT4) levels. A significant finding in all three cases was positive TSH Receptor Antibodies (TRAb), typical for GD, accompanied by very high Anti-Thyroid Peroxidase (Anti-TPO) levels, characteristic of HT. This indicates the possibility of a dual autoimmune process. Discussion: The simultaneous findings of positive TRAb and very high Anti-TPO in all three patients support the concept that GD and HT exist within a single spectrum of AITD and can coexist. The term